Reconstruction of The Inner Baduy’s Ecohouse Structure in Banten Province - Meiske Widyarti; Budi Indra Setiawan; Hadi Susilo Arifin; Arief Sabdo Yuwono (Forum Pasca Sarjana, 2012)
Environment quality has been worsening year by year; and building’s sector contributes 66% of fossil fuels pollution’s sources. The technique in building constructions needs to changing in order to increase environmental friendly manner. Indigenous people, such as the Inner Baduy community, from longstanding experience have developed systems as their local wisdoms adapting to its environment and houses in a sustainable manner. The objective of this study is to emphasize the importance of traditional knowledge in terms of providing low input energy buildings and settlement. A reconstruction of the Inner Baduy house has been drawn as a documentation of an Indonesian traditional house building in a tropical humid climate. The reconstruction is presented in a form of a technical drawings such as plan, view and section  drawing by using SkecthUp computer program. Baduy local wisdom of community is significant  in houseing structure development process. Indications by all the structure materials is taken from local sources such as rumbia roof and bamboo’s wall are taken from leuweung lembur and bantaran sungai. Development system’s local wisdom also very economic and efficient using pre-fabrication system. Key  words:  ecological design, environmental friendly, traditional building, sustainable construction